ANALISIS SWOT TERHADAP PEMBIAYAAN PRODUK MULTIJASA DI PT. BPRS AL-FALAH BANYUASIN - Elmita Sari; Meriyati Meriyati; Havis Aravik (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
BPRS Al-Falah Banyuasin itself is a financial institution that has a very important role in saving funds and distributing funds, in this activity the distribution of funds can be given to the community to obtain benefits, one of which is the benefit of services. In this case, the demand for multiservice financing products is less than other financing when viewed from the object and need. This type of research is qualitative using interviews, documentation, observation, and testing the validity of the data. The results of this study are how the swot analysis of multiservice financing at PT. BPRS Al-Falah, this Multiservice Financing Product uses a SWOT analysis, namely a comprehensive assessment of (Strength) Strengths, (Weaknesses) Weaknesses, (Opportunities) Opportunities, (Threats) Threats. The contract system for multiservice product financing is where the customer comes directly to the Bank with the aim of submitting an application for multiservice financing, then the customer must fill out a financing application form that has been provided by the bank, and is accompanied by a photocopy of an ID card.